Optimasi Biaya dan Gizi Bahan Pangan Mentah Program MBG Siswa SMP Padang Menggunakan Simpleks-Python - Andi Susanto; Alya Rozali Ramadhani; Defi Angriani; Mutia Mutia (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
The Free Nutritious Meal Program requires menu planning that is able to meet students’ nutritional needs at an efficient cost. This study aims to determine the optimal combination of raw food ingredients for the Free Nutritious Meal menu for female junior high school students aged 13–15 years in Padang City using a linear programming approach with the Simplex method assisted by Python. This research is an applied study with a quantitative approach. Food price data were obtained from local price sources in Padang City and field data from a Nutritional Fulfillment Service Unit, while nutritional composition data were based on the Indonesian Food Composition Table. Nutritional requirements were determined based on 30% of the Recommended Dietary Allowance according to the Indonesian Ministry of Health Regulation Number 28 of 2019, covering eleven nutritional components: energy, protein, fat, carbohydrates, fiber, calcium, iron, folate, vitamin A, vitamin B1, and vitamin C. Five menu combinations were formulated into a costminimization objective function with nutritional constraints, portion limits, and budget constraints. The optimization results show that three of the five menu combinations were feasible, namely K2, K4, and K5, while K1 and K3 were infeasible. The K2 combination was identified as the optimal solution and fulfilled all nutritional constraints. These findings indicate that the Python-assisted Simplex method is effective in determining an efficient, measurable, and nutritionally adequate menu composition for the Free Nutritious Meal Program.